Conservative kidney management and kidney supportive care: core components of integrated care for people with kidney failure - Davison, Sara N.; Pommer, Wolfgang; Brown, Mark A.; Douglas, Claire A.; Gelfand, Samantha L.; Gueco, Irmingarda P.; Hole, Barnaby D.; Homma, Sumiko; Kazancıoğlu, Rümeyza T.; Kitamura, Harumi; Koubar, Sahar H.; Krause, Rene; et al. (Elsevier, 2024)
Integrated kidney care requires synergistic linkage between preventative care for people at risk for chronic kidney disease and health services providing care for people with kidney disease, ensuring holistic and coordinated care as people transition between acute and chronic kidney disease and the 3 modalities of kidney failure management: conservative kidney management, transplantation, and dialysis. People with kidney failure have many supportive care needs throughout their illness, regardless of treatment modality. Kidney supportive care is therefore a vital part of this integrated framework, but is nonexistent, poorly developed, and/or poorly integrated with kidney care in many settings, especially in low- and middle-income countries. To address this, the International Society of Nephrology has (i) coordinated the development of consensus definitions of conservative kidney management and kidney supportive care to promote international understanding and awareness of these active treatments; and (ii) identified key considerations for the development and expansion of conservative kidney management and kidney supportive care programs, especially in low resource settings, where access to kidney replacement therapy is restricted or not available. This article presents the definitions for conservative kidney management and kidney supportive care; describes their core components with some illustrative examples to highlight key points; and describes some of the additional considerations for delivering conservative kidney management and kidney supportive care in low resource settings. ©Elsevier
Keywords: Conservative kidney management; Health care policy; Integrated kidney care; Kidney failure; Kidney supportive care